2009
DOI: 10.1111/j.1365-2230.2009.03243.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous squamous cell carcinoma in Calabar, southern Nigeria

Abstract: Ignorance and sociocultural factors were underlying issues in delaying treatment. Education highlighting the risk associated with chronic wounds and albinism, and the need for prevention, prompt treatment and proper surgical management, would improve prognosis with a reduction in the healthcare cost of this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 7 publications
9
19
0
2
Order By: Relevance
“…This difference is due to genetically pigmented skin of our patients whose dense epidermal melanin protects them from ultraviolet radiation [11], and therefore, preventing them from skin cancers. In the present study, Kaposi sarcoma was the most common cancer which is similar to that of several Subsaharian African studies [12,13] and different from that of developed country studies in which basal cell carcinoma was the most prevalent [3][4][5].…”
Section: Discussionsupporting
confidence: 54%
“…This difference is due to genetically pigmented skin of our patients whose dense epidermal melanin protects them from ultraviolet radiation [11], and therefore, preventing them from skin cancers. In the present study, Kaposi sarcoma was the most common cancer which is similar to that of several Subsaharian African studies [12,13] and different from that of developed country studies in which basal cell carcinoma was the most prevalent [3][4][5].…”
Section: Discussionsupporting
confidence: 54%
“…This is similar to reports from Zaria [11], Jos [12], Kano [10], and Uganda [13], but differs from Calabar [14] and Zimbabwe [15] who reported Kaposi sarcoma was their commonest cutaneous malignancy. The most prevalent site is the lower limb (Table 2), and this finding is similar to reports from Nigeria [10][11][12][13][14] and Tanzania [4]. While sun exposure is the major aetiological factor in Whites, chronic ulcers and inflammation appear to be leading risk factor in Blacks.…”
Section: Discussionsupporting
confidence: 89%
“…Two cases (5%) of basal cell carcinoma were found in this study. Literature search on the reviews of cutaneous malignancies revealed that basal cell carcinoma is uncommon in Africans because of the protective skin pigmentation from UV radiation [8][9][10][11][12][13][14]. Our findings are comparable to reports from other parts of Nigeria [8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 78%
“…7,16,17 However, studies in Calabar documented that Kaposi Sarcoma was the commonest malignancy, while melanomas were the most frequent in Benin and Tanzania. 6,12,15 In addition basal cell carcinomas were the most common skin malignancy in the United States, China and Egypt, while they accounted for only 7.1% of cancers diagnosed in this study. 18,19 These variations are due to difference in skin types amongst the different racial groups.…”
Section: Discussionmentioning
confidence: 99%